Interactions of the Cytoplasmic Domain of P-Selectin with Clathrin-coated Pits Enhance Leukocyte Adhesion under Flow - Setiadi, Hendra (The Rockefeller University Press, 1998)
Flowing leukocytes tether to and roll on P-selectin, a receptor on endothelial cells that is rapidly internalized in clathrin-coated pits. We asked whether the association of P-selectin with clathrin-coated pits contributes to its adhesive function. Under flow, rolling neutrophils accumulated efficiently on CHO cells expressing wild-type P-selectin or a P-selectin construct with a substitution in the cytoplasmic domain that caused even faster internalization than that of the wild-type protein. By contrast, far fewer rolling neutrophils accumulated on CHO cells expressing P-selectin constructs with a deletion or a substitution in the cytoplasmic domain that impaired internalization. Neutrophils rolled on the internalization-competent constructs with greater adhesive strength, slower velocity, and more uniform motion. Flowing neutrophils tethered equivalently to internalization-competent or internalization-defective P-selectin, but after tethering, they rolled further on internalization-competent P-selectin. Confocal microscopy demonstrated colocalization of α-adaptin, a component of clathrin-coated pits, with wild-type P-selectin, but not with P-selectin lacking the cytoplasmic domain. Treatment of CHO cells or endothelial cells with hypertonic medium reversibly impaired the clathrin-mediated internalization of P-selectin and its ability to support neutrophil rolling. Interactions of the cytoplasmic domain of P-selectin with clathrin-coated pits provide a novel mechanism to enhance leukocyte adhesion under flow.